Pengaruh0online0customer0review, Online0customer Rating,Price0discount Dan E-Service Quality0Terhadap Minat0beli Di Tiktok0shop (Studi Kasus Mahasiswa Universitas Islam Malang Angkatan 2019 ) - Ninda Putri Della Zeinistya; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract There are various kinds of marketplace platforms in Indonesia, Tiktok is one of the platforms that have the most interest in buying by the people of Indonesia. Buying interest is the desire to buy and own an item after receiving a stimulus from the item seen. Some of the things that affect buying interest in the Tiktok shop are online0customer reviews, online0customer0ratings, price discounts, and e-service quality. This study used a non-experimental quantitative approach, sampling using non-probability sampling using a purposive sampling technique with the criteria of active Unisma students class of 2019 and having shopped more than twice on the Tiktok social media platform. The variables used in this study are0purchase0intention0(the dependent0variable), while the independent variables are online customer reviews, online0customer reviews, price discounts, and e-service0quality. The data0analysis used in this0study is multiple0regression analysis.0The results of this study conclude that online0customer reviews, online0customer reviews, price discounts, and e-service quality variables influence purchase intention simultaneously or partially. Keywords: Online Costumer Review, Online Costumer Rating, Price Discount And E-Service Quality